Where the twain shall meet? A study of best practices to resolve retailer–supplier acrimony in post-audit recovery of trade promotion dollars. Issue 2 (2nd April 2020) - Parvatiyar, Atul; Moorthy, Janakiraman; Donthu, Naveen
Abstract: Deductions and claims to recover trade promotions incentives through post-audit of previous years' transactions is a highly contentious but prevalent practice in the industry. Retailers, given their low margins of operations, are motivated to seek every opportunity to obtain extra incentives from suppliers to boost their profits. They often hire third-party post-auditors to scrub through all their transactions and "deal sheets" or supplier agreements to search for potential unclaimed trade promotion dollars promised by suppliers in prior years. Third party auditors have an incentive to also make dubious claims as they are compensated on contingency fees of a percent of claims recovered. Such practices lead to acrimony between retailers and suppliers. They often have differing viewpoints and opinions about the contextual terms of the trade promotion deals itself leading to an opinion "chasm" that is sometimes difficult to bridge. The resulting tension among retailers and suppliers, along with regulatory compliance under the Sarbanes–Oxley Act, and prevailing questions on the role and practices of post-auditors, motivated this study. Conducted over a 24-month period with extensive collaboration and research discussions between the study team and responsible managers from leading US retail and manufacturing companies. The distinctive mix of academic rigor and practitioner relevance was the hallmark of this study that involved three retail summits conducted with industry participants to discuss the research method and its resultant findings. Evidence suggests that transactional discrepancies will continue to happen, despite technological advances, because of large volume of transactions and multiplicity of complex trade promotion methods in vogue in the retail world. So, as long as there are claim opportunities, post-audit recovery practices will continue, confounding the darker side of the retailer–supplier relationship. Through a multi-stage and multi-level study, and data from a variety of sources, we identify best practices in post-audit recovery and suggest ways to reduce associated conflict and improve relationship satisfaction.